2017
DOI: 10.3390/sports5010016
|View full text |Cite
|
Sign up to set email alerts
|

Functional Movement Screen Scores and Physical Performance among Youth Elite Soccer Players

Abstract: This study had two main objectives: (1) to determine if differences in Functional Movement Screen (FMS) scores exist between two levels of competition; and (2) to analyze the association between FMS individual and overall scores and physical performance variables of lower-limb power (jumps), repeated sprint ability and shot speed. Twenty-two Under 16 (U16) and twenty-six Under 19 (U19) national competitive soccer players participated in this study. All participants were evaluated according to anthropometrics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 36 publications
5
46
1
Order By: Relevance
“…Unexpectedly, there were no significant differences in the FMS tests between groups, except in FMSmove, where the Elite group gained higher scores than the Sub-elite players. In our study, the scores obtained in the FMStotal by the Elite group were similar to those reported by Silva et al [44] for youth Portuguese elite soccer players (FMS total = 13.8) and higher than those presented in the study by Marques et al [32] on youth athletes from a premier league soccer team (FMStotal = 12.4).…”
Section: Discussionsupporting
confidence: 90%
“…Unexpectedly, there were no significant differences in the FMS tests between groups, except in FMSmove, where the Elite group gained higher scores than the Sub-elite players. In our study, the scores obtained in the FMStotal by the Elite group were similar to those reported by Silva et al [44] for youth Portuguese elite soccer players (FMS total = 13.8) and higher than those presented in the study by Marques et al [32] on youth athletes from a premier league soccer team (FMStotal = 12.4).…”
Section: Discussionsupporting
confidence: 90%
“…17 The FMS CS was 13.2+1.7 vs. 14.5+1.5, which is lower than the youth elite soccer players completed the FMS. 21 Functional movement scores were 13.87+2.93 vs. 14.96+2.07. 21 Negligible differences were noted within individual FMS movements between the two age groups.…”
Section: Functional Movement Screen Composite Scores In Field Sportsmentioning
confidence: 93%
“…21 Negligible differences were noted within individual FMS movements between the two age groups. 21 A comparison between NCAA Division II men's and women's soccer players was conducted to assess differences in FMS CS. 19 Men's soccer scored slightly higher than women's soccer, 16 An examination of these studies suggested that injury and younger ages negatively impact FMS CS in field sport athletes.…”
Section: Functional Movement Screen Composite Scores In Field Sportsmentioning
confidence: 94%
See 2 more Smart Citations